Unlocking Spiritual Enlightenment: A Critical Study of Idries Shah’s The Way of the Sufi - Sherzad Shafie Babo Barzani; Sirwan Abudlkarim Ali (Zanco Journal of Humanity Sciences)
The Way of the Sufi (2015) stands as a significant signpost into Sufi literature, offering profound insights into the mystical tradition of Sufism, and introducing revered Sufi figures, their ideologies, and texts. This study analyses Shah's main work, focusing on its portrayal of Sufi philosophy, enlightenment practices, and transmission of spiritual knowledge through literary styles used in the book. The study argues that Sufi literature’s effective method of spiritual guidance and enlightenment is empowered by the distinctive narrative style and philosophical themes presented by the Sufis in the form of poems or stories. This study highlights the significance of Sufi literature in general, its literary style, and the spiritual accomplishments presented. A comprehensive examination of Shah’s thoughts is aimed at revealing the profound depths of Sufi teachings to offer new insights and develop an understanding of Sufi’s philosophical tenets, deep divine love, and broader cultural implications of spiritual devotion.